Development and validation of RP-HPLC method with UV-DAD detection for simultaneous determination of acesulfame K, sodium saccharin and aspartame in beverages - Jankulovska, Mirjana S.; Josimovska, Teodora; Velkoska-Markovska, Lenche (Akademiai Kiado Zrt., 2024)
Artificial sweeteners are low-calorie substances used as food additives with aim to impart a sweet taste to beverages without adding significant calories. Due to the regulatory compliance regarding the type and the amount of artificial sweetener, and due to the large consumption of beverages and the effects of artificial sweeteners on human health, their identification and quantification is of a great importance. In this research simultaneous determination of acesulfame K (ACE-K), sodium saccharin (Na-SAC) and aspartame (ASP) as the most commonly used sweeteners in beverages was performed with a reversed – phase high performance liquid chromatography (RP – HPLC) with diode array detection (DAD). The best separation of the analytes was achieved on a Poroshell 120 EC-C18 (3.0 3 50 mm, 2.7 μm) column and isocratic elution with a mobile phase consisted of acetonitrile and diluted phosphoric acid (pH 5 3.8) with 7/93 volume ratio (V/V), and ﬂow rate of 1 mL min 1. The chromatographic process was followed at 195, 220 and 230 nm, under constant column temperature (25 8C). Under these chromatographic conditions, the total time of analysis was less than 5 min. The developed method was validated for linearity, precision, accuracy, limit of detection (LOD) and limit of quantiﬁcation (LOQ). The LOD under established chromatographic conditions was 0.03, 0.07 and 0.17 mg L 1 for Na-SAC, ACE-K and ASP, respectively. The amount of artiﬁcial sweeteners in analyzed samples ranged from 30.32 to 148.37 mg L 1 for ACE-K, from 16.10 to 93.05 for Na-SAC, and from 6.06 to 512.72 for ASP. The validated method was successfully applied for determination of analytes in different commercially available beverages.
Keywords: acesulfame K, sodium saccharin, aspartame, beverages, RP-HPLC